Analisis Faktor-Faktor yang Mempengaruhi Cadangan Devisa Periode 2000-2019 - Septian Angga pratama; Yuni Prihadi Utomo (Ekonomis: Journal of Economics and Business, 2022)
Foreign exchange reserves is foreign currencies that are reserved at the central bank for the purposes of financing development and foreign transactions such as imports, foreign debt payments, investments and other financing. Foreign exchange reserves are very influential on the economic activities of a country. The amount of foreign exchange reserves can be used as an indicator to assess the country's resilience in facing the economic crisis. This study aims to determine the impact of exports, imports, inflation, exchange rates, foreign investment and foreign debt on Indonesia's foreign exchange reserves during the period 2000-2019 using the Ordinary Least Square approach. The results show that exports, foreign investment, and foreign debt have a positive effect on foreign exchange reserves, while imports and exchange rates have a negative effect on foreign exchange reserves. Meanwhile, inflation has no effect on Indonesia's foreign exchange reserves during the 2000-2019 period.